Internet and Distributed Computing Systems : 8th International Conference, IDCS 2015, Windsor, UK, September 2-4, 2015. Proceedings - Di Fatta, Giuseppe; Fortino, Giancarlo; Li, Wenfeng; Pathan, Mukaddim; Stahl, Frederic; Guerrieri, Antonio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 8th International Conference on Internet and Distributed Computing Systems, IDCS 2015, held in Windsor, UK, in September 2015. The 19 revised full and 6 revised short papers presented were carefully reviewed and selected from 42 submissions. The selected contributions covered cutting-edge aspects of Cloud Computing and Internet of Things, sensor networks, parallel and distributed computing, advanced networking, smart cities and smart buildings, Big Data and social networks.
Cloud Computing and Internet of Things.-Cloud Shield: Effective Solution for DDoS in Cloud.-Towards Modelling-based Self-adaptive Resource Allocation in Multi-tiers Cloud Systems -- Web2Compile-CoT: A web IDE for the Cloud of Things -- Fuzzy Logic Based Energy Aware VM Consolidation -- Autonomic and Cognitive Architectures for the Internet of Things -- Sensor Networks -- Sensor Web Enablement applied to an Earthquake Early Warning System -- Towards motion characterization and assessment within a wireless body area network -- Data Driven Transmission Power Control for Wireless Sensor Networks -- Mining Regularities in Body Sensor Network Data -- Smart Cities and Smart Buildings -- Task Execution in Distributed Smart Systems -- Inferring Appliance Load Profiles From Measurements -- Intra Smart Grid Management Frameworks for Control and Energy Saving in Buildings -- Urban Crowd Steering: an Overview -- Distributed Computing -- Towards a Self-Adaptive Middleware for Building Reliable Publish/Subscribe Systems -- Review of Replication Techniques For Distributed Systems -- Connectivity Recovery in Epidemic Membership Protocols -- Parallel Computing -- Optimisation Techniques for Parallel K-Means on MapReduce -- Epidemic Fault Tolerance for Extreme-Scale Parallel Computing -- A GPU-based Statistical Framework for Moving Object Segmentation: Implementation, Analysis and Applications -- Advanced Networking -- Hardware-Assisted IEEE 802.15.4 Transmissions and Why to Avoid Them -- Containment of Fast Scanning Computer Network Worms -- Fragmented-Iterated Bloom Filters for Routing in Distributed Event-Based Sensor Networks -- Big Data and Social Networks -- Fast Adaptive Real-Time Classification for Data Streams with Concept Drift -- Omentum - a Peer-to-Peer Approach for Internet-scale Virtual Microscopy -- Using social networks data for behavior and sentiment analysis -- Sentimental Preference Extraction from Online Reviews for Recommendation.
Keywords: Computer Communication Networks; Computer software; Computer security; Information storage and retrieva; Software engineering; Computer Communication Networks; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Systems and Data Security; Information Storage and Retrieval; Software Engineering